Routine Infanticide in the West 1500–1800 - Hanlon, Gregory (History compass, 2016)
Historians have assumed that early modern Europeans did not practice neo-naticide similar to the great Asian civilizations, but sex-ratio studies are only now entering the demographic literature. This article passes in review both published and unpublished research on sex ratios at baptism in Italy, France, England and colonial Acadia, together with juvenile sex ratios drawn from censuses in Germany, France and Italy. Both endemic and conjunctural imbalances appear everywhere, but they could target females or males depending upon the context.